2008
DOI: 10.1021/ja074640e
|View full text |Cite
|
Sign up to set email alerts
|

C−F Activation of Fluorinated Arenes using NHC-Stabilized Nickel(0) Complexes: Selectivity and Mechanistic Investigations

Abstract: The reaction of [Ni2((i)Pr2Im)4(COD)] 1a or [Ni((i)Pr2Im)2(eta(2)-C2H4)] 1b with different fluorinated arenes is reported. These reactions occur with a high chemo- and regioselectivity. In the case of polyfluorinated aromatics of the type C6F5X such as hexafluorobenzene (X = F) octafluorotoluene (X = CF3), trimethyl(pentafluorophenyl)silane (X = SiMe3), or decafluorobiphenyl (X = C6F5) the C-F activation regioselectively takes place at the C-F bond in the para position to the X group to afford the complexes tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
159
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(165 citation statements)
references
References 115 publications
5
159
0
1
Order By: Relevance
“…The nickel-carbon and nickel-chlorine distances are unexceptional and in a range found for other nickel-NHC complexes. [4,5] The tetrafluorophenyl bridge is almost perpendicularly orientated to the nickel coordination plane [best plane through Ni, C(1), C(19), C(10), Cl (1) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nickel-carbon and nickel-chlorine distances are unexceptional and in a range found for other nickel-NHC complexes. [4,5] The tetrafluorophenyl bridge is almost perpendicularly orientated to the nickel coordination plane [best plane through Ni, C(1), C(19), C(10), Cl (1) …”
Section: Resultsmentioning
confidence: 99%
“…[2] We have shown that zero-valent nickel-NHC (N-heterocyclic carbene) complexes are attractive for these kinds of transformations for perfluorinated as well as partially fluorinated aromatic compounds. We have demonstrated that the compound [Ni 2 (iPr 2 Im) 4 (COD)] [1; iPr 2 Im = 1,3-bis(isopropyl)imidazolin-2-ylidene; Figure 1] acts as an excellent source for the very electron-rich [3] bis(carbene)-nickel(0) complex fragment {Ni(iPr 2 Im) 2 } in C-C, C-S [4] , and C-F [5] bond-activation reactions. selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…246 Oxidative addition of arylfluorides is preceded by arene coordination and this has been shown experimentally for Ni(0) compounds which coordinate octafluoronaphthalene, 305 and fluorobenzenes. 306,307 where a new P-F bond has been formed and a cyclohexyl group is transferred from the phosphorous to the metal (Scheme 102). The reaction rate follows the order Pt > Pd, whereas the opposite (Pd > Pt) is observed in oxidative addition reactions with other non-fluorinated aryl halides.…”
Section: Oxidative Addition Of R-fmentioning
confidence: 99%
“…We speculate that the LiI-promoted C-F bond activation of 12 on Pd(PCy 3 ) 2 would take place to give the cis-oxidative addition product, and the rapid dissociation of a PCy 3 ligand then might occur due to the steric hindrance of the two bulkier PCy 3 ligands. On the basis of theoretical and experimental studies, Radius et al assumed that a related C-F bond activation of 12 on a Ni(NHC) 2 fragment, yielding trans-[Ni(NHC) 2 (C 6 F 5 )(F)], would proceed via the corresponding cis-oxidative addition product [61]. Transmetalation between A and 4 in the presence of LiI would take place to give a biarylpalladium(II) intermediate (B).…”
Section: Scheme 12mentioning
confidence: 99%
“…Radius et al reported a coupling reaction of octafluorotoluene (C 7 F 8 ) and decafluorobiphenyl (C 12 F 10 ) with arylboronic acid in the presence of a catalytic amount of NHC-nickel(0) catalyst (where NHC represents N-Heterocyclic carbene) [59]. This group also demonstrated the usefulness of a NHC-nickel(0) complex for the C-F bond activation of hexafluorobenzene (C 6 F 6 ), and the Ni(0)/NHC complex did indeed show catalytic activity toward the hydrodefluorination of C 6 F 6 [60][61][62]. However, an efficient catalytic transformation of C 6 F 6 involving a C-C bond formation is very rare.…”
Section: Introductionmentioning
confidence: 97%